2014
DOI: 10.1186/1476-511x-13-19
|View full text |Cite
|
Sign up to set email alerts
|

Unavailability of liver triacylglycerol increases serum cholesterol concentration induced by dietary cholesterol in exogenously hypercholesterolemic (ExHC) rats

Abstract: BackgroundExogenously hypercholesterolemic (ExHC) rats develop hypercholesterolemia and low hepatic triacylglycerol (TAG) levels when dietary cholesterol is loaded. The responsible gene Smek2 was identified via linkage analysis using the original strain Sprague–Dawley (SD) rats. In this study, we compared SD and ExHC rats to investigate a relationship between hypercholesterolemia and the low hepatic TAG levels observed in ExHC rats.MethodsMale 4-weeks-old ExHC and SD rats were fed a 1% cholesterol diet for 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In our previous studies, we identified Smek2 as one of the genes responsible for DIHC in ExHC rats [15], and we revealed that Smek2 dysfunction causes impairment of de novo fatty acid synthesis in the liver of ExHC rats to develop DIHC via β-migration of secreted VLDL [15,16]. High sucrose diet is known to activate hepatic fatty acid synthesis [25].…”
Section: Plos Onementioning
confidence: 98%
See 3 more Smart Citations
“…In our previous studies, we identified Smek2 as one of the genes responsible for DIHC in ExHC rats [15], and we revealed that Smek2 dysfunction causes impairment of de novo fatty acid synthesis in the liver of ExHC rats to develop DIHC via β-migration of secreted VLDL [15,16]. High sucrose diet is known to activate hepatic fatty acid synthesis [25].…”
Section: Plos Onementioning
confidence: 98%
“…In this study, we conducted two experiments with three types of diet, different ratios of carbohydrates (glucose, sucrose, and fructose). As we reported, ExHC rats show low FAS activities even though being fed the high-sucrose diet [16]. Therefore, we conducted the experiment 1 with a hypothesis that ExHC rats had an impaired metabolism of fructose, which can skip the rate-limiting reaction of glycolysis and be more rapidly metabolized than glucose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that rats [7], mice [8], rabbits [9], guinea pig [10], hamster [11], and gerbil [12] are used for modeling human HLP. Among them, rats, hamster and mice are the most extensively used animals [13][14][15][16][17][18][19]. However, the molecular basis of pathogenesis in hyperlipidemic rats, hamster and mice model induced by HFD remain unclear, which limits its predictability and accuracy on evaluating lipid-lowering agents for human HLP.…”
Section: Introductionmentioning
confidence: 99%